Decoupling Standards from Practice: The Impact of In-House Certifications on Coffee Farms' Environmental and Social Conduct. (August 2017) - Giuliani, Elisa; Ciravegna, Luciano; Vezzulli, Andrea; Kilian, Bernard
Highlights: In the coffee industry, in-house certifications by global buyers are on the rise. Certified coffee farms are more environmentally (but not socially) sustainable. Farms' social conduct depends on their home country institutional strength. Certified farms' environmental conduct is better when they sell to cooperatives. Certified farms' environmental conduct improves in institutionally weak countries. Summary: In this paper we investigate whether coffee farms that have been granted in-house socio-environmental certification from a global buyer, display better social and environmental conduct compared to non-certified farms. We perform an econometric analysis using data from an original cross-country survey covering 575 farms in various regions of Brazil, Colombia, Costa Rica, Guatemala, and Mexico. We find that farms that have been granted in-house certification demonstrate better environmental but not better social conduct than non-certified farms. We find also that the positive relationship between in-house certification and environmental conduct is stronger if the farm sells to a cooperative, and if it is located in an institutionally weak country. Finally, we find that the institutional strength of the farm's home country has a positive influence on its social conduct. We discuss how our analysis contributes to the literature on the social and environmental impacts of certifications, and to scholarship in global value chains' social and environmental upgrading.